(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the issues of development of physical fitness of 5-7 year old gymnasts are highlighted, and the methods of scientific and methodical literature analysis, pedagogical observation, pedagogical experience, testing, and mathematical statistics were used during the research. The analysis of the results of the conducted research is presented and the final recommendations are developed. Of the 9 tests studied in the control group, only three (long jump, 900 leg raise on the gymnastic wall, and bridge standing exercise) showed improvements during the experiment with a low level of statistical reliability (P<0.05). ’changed, the change of the rest was found to be statistically unreliable (P˃0.05). In the experimental group, it was observed that the changes in all the studied tests were statistically reliable at a good (P<0.01) and high (P<0.001) level.